Shades of Grey : Anglo-German Diplomacy and Eyre Crowe, 1905-1914 - Jarvis, Elissa (East Carolina University, 2010)
In January of 1907, British Foreign Official Eyre Crowe wrote a memorandum detailing the present relations between Great Britain, France and Germany. In this memorandum, Crowe argued that war between Britain and Germany could not be avoided for long. This study examines Eyre Crowe's influence in the British Foreign Office. It argues that Crowe had significant influence in the foreign office and that he was correct with what he argued in the 1907 memorandum. Using primary documents from both the British Foreign Office and the German government, this thesis contends that the 1907 memorandum caused increased hostility towards the German Government from the British Foreign Office. This hostility made British leaders unlikely and sometimes unwilling to cooperate with the German government in a series of diplomatic events. These events included the First and Second Moroccan crises, the building of the German navy and the Baghdad railway and ultimately culminated with the July Crisis in 1914. It was what Crowe argued in his memorandum coupled with the increased hostility towards the German government that led Great Britain into entering the First World War.
Keywords: History, European; History, Modern; WW I; World War I; World War, 1914-1918--Causes; Crowe, Eyre, 1824-1910; Great Britain. Foreign Office; Great Britain--Foreign relations--20th century; Germany--Foreign relations--20th century; Moroccan Crisis, 1904-1906; Agadir Incident, 1911; Europe--History--July Crisis, 1914